Insurance companies’ trading behaviour during the European sovereign debt crisis: Flight home or flight to quality? - Bijlsma, Melle; Vermeulen, Robert (Journal of Financial Stability, 2016)
This paper empirically investigates if insurers exhibited a flight home or flight to quality during the European sovereign debt crisis and other stages of the financial crisis. Our dataset consists of over sixty insurance companies, for which we separately observe trading behaviour and portfolio revaluations at a quarterly frequency during 2006–2013. When explaining insurers’ trading behaviour we explicitly control for country risk and momentum strategies. The results show that insurers exhibited a flight to quality during the European sovereign debt crisis, while we find no evidence of a flight home. The flight to quality was not present before the European sovereign debt crisis and disappeared after ECB chairman Draghi's speech mid-2012. Interestingly, supervisory data suggests that the observed flight to quality was not driven by regulatory solvency constraints.